2019
DOI: 10.7554/elife.39595
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping cis-regulatory variants in diverse human populations

Abstract: Genome-wide association studies (GWAS) are a powerful approach for connecting genotype to phenotype. Most GWAS hits are located in cis-regulatory regions, but the underlying causal variants and their molecular mechanisms remain unknown. To better understand human cis-regulatory variation, we mapped quantitative trait loci for chromatin accessibility (caQTLs)—a key step in cis-regulation—in 1000 individuals from 10 diverse populations. Most caQTLs were shared across populations, allowing us to leverage the gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 53 publications
(117 reference statements)
1
58
0
Order By: Relevance
“…Even without covalent modifications, some TFs known as pioneer factors can establish open chromatin by binding nucleosomal DNA (Zhu et al, 2018) and either displacing nucleosomes directly or recruiting chromatin remodelers (Spitz and Furlong, 2012). Quantitative trait locus (QTL) analysis suggests that the resulting changes in chromatin accessibility contribute to TFs' influence on long-range 3D genome organization (Tehranchi et al, 2019). These indirect, chromatin-mediated effects may provide a means by which TFs with only transient binding to DNA can trigger more enduring changes to chromosome conformation and ultimately gene expression.…”
Section: Chromatin Modificationmentioning
confidence: 99%
“…Even without covalent modifications, some TFs known as pioneer factors can establish open chromatin by binding nucleosomal DNA (Zhu et al, 2018) and either displacing nucleosomes directly or recruiting chromatin remodelers (Spitz and Furlong, 2012). Quantitative trait locus (QTL) analysis suggests that the resulting changes in chromatin accessibility contribute to TFs' influence on long-range 3D genome organization (Tehranchi et al, 2019). These indirect, chromatin-mediated effects may provide a means by which TFs with only transient binding to DNA can trigger more enduring changes to chromosome conformation and ultimately gene expression.…”
Section: Chromatin Modificationmentioning
confidence: 99%
“…To call the TCF21 binding (bQTL), chromatin accessibility (caQTL), and chromosomal looping (clQTL) quantitative trait loci, we employed a published regressionbased approach which uses post-assay allele frequencies together with genotypes of each sample to infer the proportion of each sample in the pool [9,13]. Comparing the pre-assay vs. post-assay allele frequencies allows the identification of outlier SNPs where these frequencies are significantly different from one another, which indicates a cis-acting QTL variant.…”
Section: Bqtl Caqtl and Clqtl Calling In Pooled Hcasmc Linesmentioning
confidence: 99%
“…The regulatory variants that modulate other genomic features have also been characterized. QTLs for histone modification and chromatin accessibility and more recently chromosomal looping have also been mapped [9][10][11][12]. Such efforts have provided important information regarding the regulatory structure of the non-coding sequence in the genome and identified how such variation may regulate the risk for complex human disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that some TFs called pioneer factors can establish chromatin accessibility by replacing or binding nucleosome DNA or by recruiting chromatin-remodeling agents [13,14]. Quantitative trait locus (QTL) analysis and 3D genome assembly have shown that changes in chromatin accessibility ultimately alter the long-range effects of TFs [15]. Therefore, it is especially important to study the interaction mechanism between TFs and chromatin accessibility during muscle development.…”
Section: Introductionmentioning
confidence: 99%